Pemanfaatan Game Edukasi Kahoot dalam Membangun Suasana Belajar yang Menyenangkan di MI As Shaffah Bengkulu - Naziroh, Nikmatun; Febriani Melinda Putri; Dwi Putri Oktaviani; Khodijah (Yayasan Darussalam Bengkulu, 2025)
In today's digital era, the utilization of technology in learning is one of the solutions to create an interesting and fun learning atmosphere. Monotonous and teacher-centered learning often causes boredom in students, resulting in decreased motivation and learning outcomes. One of the innovations that has begun to be widely applied is the use of educational games such as Kahoot!, a digital-based interactive quiz platform that combines elements of games with education. Kahoot allows students to learn competitively while still having fun, increasing active participation and engagement in the learning process. This research was conducted at MI As Shaffah Bengkulu to describe the utilization of Kahoot in building a more fun and interactive learning atmosphere. The results of this study are expected to provide an overview that the use of educational game-based learning media is able to increase students' enthusiasm, focus and motivation to learn.